2009
DOI: 10.1007/s11606-009-1176-5
|View full text |Cite
|
Sign up to set email alerts
|

Does Price Transparency Legislation Allow the Uninsured to Shop for Care?

Abstract: BACKGROUND:The majority of states have enacted price transparency laws to allow patients to shop for care and to prevent price discrimination of the uninsured. In California, hospitals must provide a price estimate to a requesting uninsured patient and cannot bill for an amount greater than the reimbursement the hospital would receive from a government payer. OBJECTIVE:To assess the response rate of California hospitals to a patient price request and to compare the price estimates received to Medicare reimburs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 6 publications
1
25
0
Order By: Relevance
“…Viewed from an alternative perspective, only 60% of the top-ranked hospitals and 63% of the nontop-ranked hospitals were able to provide a complete price even after multiple calls to both hospitals and affiliated physician practices. Our results expand on the work of Farrell et al, 13 who mailed letters to 353 California hospitals in 2007 on behalf of fictitious patients requesting price estimates for 1 of 3 alternative elective procedures (a laparoscopic cholecystectomy, a hysterectomy for fibroids, or a routine screening colonoscopy). The investigators obtained an overall response rate of only 28% and found that only 3% of hospitals (10% of responding hospitals) were able to provide complete price estimate (hospital fee and physician fee).…”
Section: Commentsupporting
confidence: 67%
See 1 more Smart Citation
“…Viewed from an alternative perspective, only 60% of the top-ranked hospitals and 63% of the nontop-ranked hospitals were able to provide a complete price even after multiple calls to both hospitals and affiliated physician practices. Our results expand on the work of Farrell et al, 13 who mailed letters to 353 California hospitals in 2007 on behalf of fictitious patients requesting price estimates for 1 of 3 alternative elective procedures (a laparoscopic cholecystectomy, a hysterectomy for fibroids, or a routine screening colonoscopy). The investigators obtained an overall response rate of only 28% and found that only 3% of hospitals (10% of responding hospitals) were able to provide complete price estimate (hospital fee and physician fee).…”
Section: Commentsupporting
confidence: 67%
“…While pricing transparency initiatives such as CastLight Health (http://www .castlighthealth.com) have garnered widespread media attention, 11 there is very little peer-reviewed research addressing the availability of price data for medical services. 12,13 It is unclear how feasible it may be for patients to obtain pricing data for common medical services and how price estimates might vary by health care provider.…”
mentioning
confidence: 99%
“…The opacity and confusion surrounding medical costs is well documented. 29,30 Price disclosure and effective transparency initiatives would benefit not only consumers of health care but also providers in working toward cost-conscious health care delivery. From an education standpoint, while the task may be daunting, the process of developing a cost curriculum would in itself be informative for the local clinical microsystem, and the ensuing debates could contribute to a more informed national discussion of medical costs.…”
Section: Discussionmentioning
confidence: 99%
“…This would allow consumers to calculate balance bill amounts for individual service units, although it would still be difficult to calculate total out-of-pocket payments for an episode of care. It should be noted that previous efforts at public reporting of cost information have not been widely used by consumers, possibly because information is not presented in ways that are meaningful or accessible (Farrell et al 2010;Tu and Lauer 2009; U.S. Government Accountability Office 2011).…”
Section: Discussionmentioning
confidence: 99%